Association between isoenzymatic phenotypes and resistance to the fungus Microcyclus ulei P. Henn. (v.Arx.) in rubber tree clones - Kalil Filho A N; Del; Lama M A; Mestriner M A (Brazilian Journal of Genetics, 1995)
Electrophoretic analysis of 78 clones from various species and interspecific hybrids of Hevea was carried out in starch gel to detect associations between isoenzyme phenotypes of 7 enzyme systems and resistance to the leaf blight caused by M.ulei. Associations between resistance and particular phenotypes (phosphoglucose isomerase [glucose-6-phosphate isomerase] Pgi 4-3, phosphogluconate dehydrogenase 6Pgd 2-1 and malate dehydrogenase Mdh1 4-2) indicated that selection for resistance on the basis of these markers would be possible.
Source Year: 1996
Keywords: Isoenzymatic resistance; Microcyclus ulei